2019
DOI: 10.2134/agronj2019.03.0215
|View full text |Cite
|
Sign up to set email alerts
|

Response of Maize Productivity and Resource Use Efficiency to Combined Application of Controlled‐Release Urea and Normal Urea under Plastic Film Mulching in Semiarid Farmland

Abstract: Controlled‐release urea is considered to enhance crop yields while reducing labor costs from fertilizer dressing, but the impacts can range widely depending on water availability in soil. Therefore, we conducted a 3‐yr field study to evaluate the potential role of controlled‐release urea in improving productivity and resource use efficiency of maize in semiarid areas in China. Treatments were established as two mulching modes (plastic film mulching [FM] and no mulching [NM]) and three nitrogen application mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…In our study, the RMU, RMC, and RMCU increased soil water content (Fig. S2), hence effectively maintaining the high yield of potato (Table 4), which is consistent with the report by Tang et al 32 . The key to a trade-off between yield, profit, and the environment in crop production is to achieve synchronization between N supply and crop demand to avoid N excess or deficiency.…”
Section: Yearsupporting
confidence: 92%
“…In our study, the RMU, RMC, and RMCU increased soil water content (Fig. S2), hence effectively maintaining the high yield of potato (Table 4), which is consistent with the report by Tang et al 32 . The key to a trade-off between yield, profit, and the environment in crop production is to achieve synchronization between N supply and crop demand to avoid N excess or deficiency.…”
Section: Yearsupporting
confidence: 92%
“…Most of the initial experiments have shown that smaller farmlands contribute to higher agricultural production as they are more productive. Small‐scale farmers know how to use their limited resources to increase production 51‐53 . Furthermore, farmers who are small‐scale in financial capital show a significantly negative influence (mean effect: −1552.68 kg ha −1 , P ≤ 0.05) on agricultural productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Small-scale farmers know how to use their limited resources to increase production. [51][52][53] Furthermore, farmers who are small-scale in financial capital show a significantly negative influence (mean effect: −1552.68 kg ha −1 , P ≤ 0.05) on agricultural productivity.…”
Section: Meta-regressions On Previous Researchmentioning
confidence: 99%
“…Although the price of urea is low, the cost of topdressing is high, and the high cost but labor saving feature of the NC treatment might be a tradeoff in terms of practical production [54,55]. Our previous study showed that the NC treatment obtained higher net return than the NU treatment [56,57]. Therefore, the NC treatment might be a better N application type, which increased root distribution in the deep soil layer and improved the use of deep soil water in the arid and semi-arid climate of the Loess Plateau.…”
Section: Discussionmentioning
confidence: 99%